(untitled) (GENDER EQUALITY: International Journal of Child and Gender Studies, 2021)
Language skills, the key elements for children’s development, are often used as a benchmark to measure the development of all abilities he/she possessed. For early childhood, time spent at school is an opportunity for them to develop their language skills, especially expressive language. The storytelling method often found in PAUD is still less innovative. This triggers boredom and result in neglecting learning process that is detrimental to students, especially in improving expressive language skills. The use of relevant techniques in extratextual activities during the learning process combined with the storytelling method will be very helpful for children. There are 12 extratextual techniques for teachers to do and nine techniques that can be done by children. These two categories of extratextual activities can make the storytelling method richer and ensure the achievement of learning targets specifically related to children’s language acquisition. This extratextual activity can trigger the development of children’s expressive language in terms of adding new vocabulary, increasing the meaning of old and new vocabulary and developing vocabulary into sentences in everyday conversation. The conditioning carried out in the application of this extratextual activity also has a positive influence in terms of four aspects of language development, namely the development of phonology, semantics, grammar and pragmatics. In phonology, children are strengthened how to pronounce the alphabet correctly; in semantics, children get meaning reinforcement and additional meaning from a vocabulary; on grammar and pragmatics, improvement is given to the arrangement of correct grammar when old and new vocabulary is used in conversation.